MENDESAIN PEMBELAJARAN FIKIH DENGAN METODE SIMULASI - Ulfah Hayati Muzayanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
To improve the quality of teaching and learning processes need to use innovative strategies and methods in the learning process. It is important that teachers do not seem monotonous learning process. Empirically prove that the monotony of learning can result in saturation of students. If a student is sick and tired, it will result in lower student interest in learning that ultimately results in declining student achievement as well. Teachers in implementing the learning should select methods appropriate to students' abilities and to foster interest and creativity of students. Various alternative methods can be used by teachers in making learning in the classroom, one method of simulation. The application of simulation methods have four phases: the orientation phase, participation in training, simulation itself, and frequently asked questions. While the role of teachers in the simulation method is explained, umpiring, coaching and discussion.